Firm Size, Market Risk, And Return Reversal Anomalies During The COVID-19 Pandemic - Ferikawita M. Sembiring (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2024)
This research aims to prove whether firm size and market risk based on CAPM affect return reversal anomalies as indicators of market overreaction during the COVID-19 pandemic. This explanatory research used a sample of stocks on the Indonesia Stock Exchange (IDX) that could be profitable during the pandemic period up to the effective period of phase one and two vaccination. It was found that return reversal anomalies occurred in the short term on the IDX, and contrarian strategies resulted in profits. Factors of firm size and market risk affected the reversal of returns in specific periods but did not affect other periods. When firm size and market risk had no effect, the return reversal anomaly occurred entirely due to the investors' overreaction in response to the pandemic without regard to the size and market risk factors of companies whose stocks were the investment target.